A Complex Role for Lipocalin 2 in Bone Metabolism: Global Ablation in Mice Induces Osteopenia Caused by an Altered Energy Metabolism. (24th March 2018) - Capulli, Mattia; Ponzetti, Marco; Maurizi, Antonio; Gemini‐Piperni, Sara; Berger, Thorsten; Mak, Tak Wah; Teti, Anna; Rucci, Nadia
ABSTRACT: Lipocalin 2 (Lcn2) is an adipokine that carries out a variety of functions in diverse organs. We investigated the bone phenotype and the energy metabolism of Lcn2 globally deleted mice ( Lcn2 –/– ) at different ages. Lcn2 –/– mice were largely osteopenic, exhibiting lower trabecular bone volume, lesser trabecular number, and higher trabecular separation when compared to wild‐type (WT) mice. Lcn2 –/– mice showed a lower osteoblast number and surface over bone surface, and subsequently a significantly lower bone formation rate, while osteoclast variables were unremarkable. Surprisingly, we found no difference in alkaline phosphatase (ALP) activity or in nodule mineralization in Lcn2 –/– calvaria osteoblast cultures, while less ALP‐positive colonies were obtained from freshly isolated Lcn2 –/– bone marrow stromal cells, suggesting a nonautonomous osteoblast response to Lcn2 ablation. Given that Lcn2 –/– mice showed higher body weight and hyperphagia, we investigated whether their osteoblast impairment could be due to altered energy metabolism. Lcn2 –/– mice showed lower fasted glycemia and hyperinsulinemia. Consistently, glucose tolerance was significantly higher in Lcn2 –/– compared to WT mice, while insulin tolerance was similar. Lcn2 –/– mice also exhibited polyuria, glycosuria, proteinuria, and renal cortex vacuolization, suggesting a kidney contribution to their phenotype. Interestingly, the expression of the glucose transporter protein type 1, that conveys glucose into the osteoblasts and is essential for osteogenesis, was significantly lower in the Lcn2 –/– bone, possibly explaining the in vivo osteoblast impairment induced by the global Lcn2 ablation. Taken together, these results unveil an important role of Lcn2 in bone metabolism, highlighting a link with glucose metabolism that is more complex than expected from the current knowledge. © 2018 American Society for Bone and Mineral Research.